Prenatal diagnosis of genetic disorders. - Niermeijer, M F (1976)
Three hundred and fifty pregnancies were monitored by transabdominal amniocentesis in the fourteenth to sixteenth week of gestation followed by karyotyping or biochemica assays of cultured amniotic fluid cells and analysis of alpha-fetoprotein in the amniotic fluid supernatant. The pregnancy was interrupted in 36 cases (10%) either becasue of a fetal abnormality or the presence of a male fetus in pregnancies at risk for an X-linked disease. Four chromosomal aberrations were found in 87 pregnancies tested because of advanced maternal age. In 101 pregnancies with a recurrence risk of Down's syndrome, 2 fetuses with an abnormal karyotype were detected. In 11 cases, in which 1 parent was a carrier of a balanced translocation, 2 unbalanced fetal karyotypes were found. Fetal chromosome studies in 43 pregancies at risk for an X-linked disease indicated the presence of a male fetus in 21 cases. Prenatal diagnosis of 11 different metabolic diseases was performed in a total of 34 cases. Microchemical techniques were used to allow completion of the diagnosis of seven different enzyme deficiencies within 9 to 22 days after amniocentesis. Alpha-fetoprotein assay in the amniotic fluid supernatant of 47 pregnancies at risk for an open neural tube defect resulted in the detection of 3 anencephalic fetuses during the second half of pregnancy. The safety and reliability of amniocentesis and the possible effects on the outcome of pregnancy are evaluated. Prenatal diagnosis offers a promising alternative for parents who are at risk of having a child with a genetic disease which can be detected in amniotic fluid or in cultured amniotic fluid cells.